Catering for the athletes village at the Sydney 2000 Olympic Games: The role of sports dietitians - Pelly, F.; O'Connor, H.; Denyer, G.; Caterson, I. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
This article describes the development, analysis, and implementation of the menu available to athletes and patrons in the main dining hall of the Athletes Village at the Sydney 2000 Olympic Games and the significant role of sports dietitians in this process. Menu design and development was informed by focus groups, literature reviews, and food-preference surveys of athletes. The final menu was also assessed by an expert panel of Australian sports dietitians. A custom-designed database (Foodweb) was developed to enable dietary analysis of food-production data and creation of point-of-choice nutrition labels. Dietitians assisted with quality assurance testing and training of catering staff. Athletes surveyed in the main dining hall (N = 414) agreed that the menu contained sufficient variety and adequate meat, pasta/rice, vegetable/ salad, fruit, and snack items. Sports dietitians played a significant role in ensuring that the menu met the needs of athletes from a range of differing cultural and sporting backgrounds. Dining-hall patrons provided positive feedback and few complaints about the overall dining experience. The information presented in this report can help future caterers and dietitians with the planning and provision of suitable food for athletic performance at an Olympic Games.